Gambaran Klinis Pasien Terduga Tuberkulosis Paru Resisten Obat (TB-RO) dengan Kolonisasi Candida sp. di Rumah Sakit Hasan Sadikin Bandung - Zalfa, Hasna Rafifah Zahira; Kulsum, Iceu Dimas; Suryadinata, Hendarsyah; Chrysanti, Chrysanti; Dewi, Intan Mauli Warma (Jurnal Penyakit Dalam Indonesia, 2024)
Introduction. Candida sp. is a fungus that lives as a commensal in human body, but may cause infection upon immune suppression. The decrease in immunity due to TB infection and long-term use of antibiotics in TB patients may increase the risk of the Candida sp. colonization in patient. Data regarding the prevalence of Candida sp. colonization in TB patients and its impact has not been widely reported. This study was conducted to determine the prevalence and clinical characteristics of presumptive drug-resistance TB patients with Candida sp. colonization. Methods. A cross-sectional study was conducted using secondary data from a previous study in 2018 at the DR-TB clinic in Hasan Sadikin General Hospital Bandung, Indonesia. Patients who were included in the study were aged 18 years or above, presented with pulmonary TB symptoms, and had minimum 5 months of TB treatment history. Candida sp. growth on sputum was examined by culture on CHROMagar® media. Results. One hundred and twenty-two patients met the inclusion and exclusion criteria. The prevalence of Candida sp. colonization in presumptive drug-resistance TB patients was 54.9%. The species found were mostly Candida albicans (71.6%), Candida glabrata and Candida parapsilosis (14.9%), and Candida tropicalis (5.9%). The predominant symptoms of pulmonary tuberculosis included a persistent cough lasting two weeks or longer and productive cough (100%), while the most frequently observed abnormalities on radiological scans were nodules and patchy lesions (98.5%). There were no significant differences between patients with positive and negative Candida sp. colonization. Conclusions. More than 50% of presumptive drug-resistant TB patients at the MDR-TB clinic in Hasan Sadikin General Hospital had positive results of Candida sp. culture on their sputum. The most common clinical manifestations were coughing for 2 weeks or more, productive cough, hemoptysis, fever, chest pain, shortness of breath, night sweats, weight loss, and reduced appetite. Future studies should be conducted to determine the long-term outcome of fungal colonization in these patients.